(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This paper examines the analysis of the structure of automotive terms in English and Uzbek. Automotive terminology is a specific vocabulary that includes terms related to the design, operation, and maintenance of automobiles. The purpose of the study is to identify the features of the formation and functioning of automotive terms in two languages, as well as to analyze their semantic.